'Walter Benjamin's Philosophy of Language'. Issue 6 (June 2014) - Procyshyn, Alexei
Abstract In this article, I reconstruct Walter Benjamin's philosophy of language and refine the non‐predicational view of meaning often attributed to him. By situating his 1916 essay 'On Language as Such and on the Language of Man' within the context of his struggle with Russell's paradox and its implications for phenomenology, I show how Benjamin arrives at his conception of non‐conceptual content as an environmentally embedded affordance that is directly apprehended by appropriately situated and capable agents. This affordance‐like character of meaning explains Benjamin's account of communication, Adamic naming, and his famous distinction between linguistic and spiritual essences (sprachliche‐ and geistige Wesen). I conclude by showing why translation is central to his views on expression and communication and how it reinforces his account of language‐use.